Фізичні властивості монокристалів g-фази взаємної системи CuInSe2 + 2CdТеÛ CuInТе2 + 2CdSe - Олексеюк, Іван Дмитрович; Лавринюк, Зоряна Володимирівна; Парасюк, Олег Васильович; Юрченко, Оксана Миколаївна; Змій, Ольга Федорівна; Olekseiuk, Ivan D.; Lavryniuk, Zoriana V.; Parasiuk, Oleh V.; Yurchenko, Oksana M.; Zmii, Olha F. (Волинський національний університет імені Лесі Українки, 2010)
Досліджено фізичні властивості монокристалів g-фази, вирощених модифікованим методом Бріджмена по перерізу CuInSe2–2CdTe системи CuInSe2 + 2CdTe Û CuInTe2 + 2CdSe. Визначено ширину забороненої зони цих кристалів за спектрами поглинання. Електричні властивості кристалів досліджували вимірюваннями ефекту Холла і температурної залежності провідності кристалів. The physical properties of the single crystals of the g-phase grown by modified Bridgman method of the CuInSe2 + 2CdTe ÛCuInTe2 + 2CdSe system have been investigated. The band gap of these crystals from the absorption spectra was defined. The electrical properties of the crystals were determined by measuring the Hall effect and temperature dependence of the crystal conductivity.
The Phisycal Properties of the γ-Phase Single Crystals of the Reciprocal System CuInSe2 + 2CdTe ÛCuInTe2 + 2CdSe
Keywords: фазові рівноваги; халькогенідні напівпровідники; ширина забороненої зони; the phase diagrams; chalcogenide semiconductors; band gap